A Study on Dietary Habits and their Impact on Obesity and Menstrual Pattern among the Girls In KM/ Al-Matheena Maha Vidyalaya, Nintavur - Haaney, R.Z.; Nazeem, M.H.M. (Faculty of Indigenous Medicine, University of Colombo, 2025)
Obesity and its related health problems have emerged as significant public health concerns, particularly among young female students. The objective of this survey was to study the dietary habits and their effects on obesity and menstrual patterns among the female students at KM/Al-Matheena Maha Vidyalaya in Nintavur situated in the Eastern Province of Sri Lanka. In this survey, a cross-sectional study design was used. Quantitative data was collected by using anthropometric measurements and structured questionnaires on meal frequency, food category intake, typical food for each meal, water intake, physical activities, and menstruation to assess the objectives of this survey. Random sampling was used to select 209 participants aged between 10-18 years who gave consent. The findings reveal a deviation from the traditional diet habits towards calorie-densed, poor nutrient foods like fast and processed foods. Results reveal that 62.68% of them have normal weight. However, the BMI of 18.66% of rest of the participants are at risk of overweight, overweight, and obese and rest are underweight and majority of those who have higher than normal BMI have disturbed menstrual pattern also. This study further reflects the alarming prevalence of obesity among adolescent girls and their impact on menstrual pattern. In conclusion it is proposed to educate the community to encourage healthy eating habits, to enhance physical activities through awareness programmes among the students and the parents. It is further recommended to conduct a large-scale community-based awareness programmes in order to propagate the harmful unhealthy eating habits and its adverse consequences.
Keywords: Dietary habits; Obesity; Menstrual irregularities; Adolescent girls; anthropometric measurements